Aloe vera: A Sustainable Green Alternative to Exclude Antibiotics in Modern Poultry Production - Rifat Ullah Khan; Shabana Naz; Davide De Marzo; Michela M. Dimuccio; Giancarlo Bozzo; Vincenzo Tufarelli; Caterina Losacco; Marco Ragni (MDPI AG, 2022)
Over the past 50 years, there has been a rapid increase in the need for poultry meat on a global scale to meet the rising demand from health, ecology, safety and equity. However, there has been a significant rise in recent years in both public demand and scientific interest for organic poultry farming, particularly when using medicinal herbs due to the rising concern of antibiotic resistance in end users. Ban on the use of antibiotics in the poultry industry has resulted in the demand of herbs as alternatives to antibiotics. Various research efforts have illustrated the nutritional value of Aloe vera in improving growth performance and immune status and acting as an antibacterial and anticoccidial agent in poultry. Aloe vera has been used as a supplement in the form of gel, alcoholic extract, powder, polysaccharide and aqueous extract. Aloe vera contains more than 200 nutrients, bioactive compounds, polysaccharides and saponins. In the current review, we have detailed the effect of Aloe vera as an alternative to antibiotics on growth performance, antimicrobial and antiparasitic activities and blood biochemical alternations in poultry.